Polska wersja Wzniesienia Milena Ruskowa - Rikev, Kamen (Przekłady Literatur Słowiańskich, 2019)
The article comments on Milen Ruskov’s third novel Summit (The Heights / Възвишение, 2011) and its critical acclaim in Bulgaria. Set in 19th-century milieu, the revolutionary struggles and the novel’s unique language have been indicated by critics as its most outstanding aspects that provoke new debates on the national and linguistic identity of contemporary Bulgarians. At the same time the novel’s Polish translation by Magdalena Pytlak (Wzniesienie, 2017) poses other questions concerning the promotion of modern Bulgarian culture abroad, the translatability of Ruskov’s work and the translator’s strategies in terms of successfully “importing” Bulgarian literature into the Polish context.